2010
DOI: 10.1016/j.neuropharm.2010.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Disease-modifying activity of progesterone in the hippocampus kindling model of epileptogenesis

Abstract: Progesterone (P) is an endogenous anticonvulsant hormone. P is being evaluated as a treatment for epilepsy, traumatic brain injury, and other complex neurological conditions. Preclinical and clinical studies suggest that P appears to interrupt epileptogenic events. However, the potential disease-modifying effect of P in epileptogenic models is not widely investigated. In this study, we examined the effects of P on the development of hippocampus kindling in female mice. In addition, we determined the role of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 68 publications
4
56
0
2
Order By: Relevance
“…In recent years, numerous studies have confirmed the powerful anticonvulsant activity of progesterone in diverse animal seizure models (see Reddy, 2009). Recent studies in our lab confirm the antiepileptogenic effects of progesterone in the kindling model of epileptogenesis (Reddy et al, 2010; Reddy and Mohan, 2011). There are two mechanisms by which progesterone affects reproduction and seizure susceptibility: binding to progesterone receptors (PRs) and being metabolized to the neurosteroid allopregnanolone.…”
Section: Neuroendocrine Mechanisms Of Catamenial Epilepsysupporting
confidence: 60%
See 1 more Smart Citation
“…In recent years, numerous studies have confirmed the powerful anticonvulsant activity of progesterone in diverse animal seizure models (see Reddy, 2009). Recent studies in our lab confirm the antiepileptogenic effects of progesterone in the kindling model of epileptogenesis (Reddy et al, 2010; Reddy and Mohan, 2011). There are two mechanisms by which progesterone affects reproduction and seizure susceptibility: binding to progesterone receptors (PRs) and being metabolized to the neurosteroid allopregnanolone.…”
Section: Neuroendocrine Mechanisms Of Catamenial Epilepsysupporting
confidence: 60%
“…Recent studies suggest that neurosteroids play a role in epileptogenesis (Edwards et al, 2001; Biagini et al, 2006; 2009a; 2010; Reddy et al, 2010; Reddy, 2013a). Using the kindling model, we demonstrated that the development and persistence of limbic epileptogenesis are impaired in mice lacking progesterone receptors (Reddy and Mohan, 2011).…”
Section: Anticonvulsant and Antiepileptogenic Activity Of Neurosteroidsmentioning
confidence: 99%
“…In contrast to benzodiazepines, where utility in the chronic treatment of epilepsy is limited by tolerance, anticonvulsant tolerance is not evident with neurosteroids [56, 57]. Recent studies suggest that neurosteroids play a role in epileptogenesis [58, 59]. Thus, there is considerable interest in leveraging the growing understanding of neurosteroid modulation of GABA-A receptor function to mitigate epilepsy symptomatology.…”
Section: Epilepsymentioning
confidence: 99%
“…It has been shown that functional inactivation of synaptic GABA-A receptors via active internalization is the physiologic mechanism by which benzodiazepine resistance rapidly emerges in refractory SE [79, 80]. Therefore, neurosteroid compounds like AP and its synthetic derivatives, which potentiate both phasic and tonic current, have been proposed as potential alternatives [12, 58, 81]. A randomized, double-blind, placebo-controlled, add-on, Phase II clinical trial is underway to evaluate SGE-102, an intravenous formulation of AP [82].…”
Section: Status Epilepticusmentioning
confidence: 99%
“…Progesterone is a neurosteroid that could potentially have immunosuppression effects and contributions to neuronal excitability changes; firing to neurotransmitters are suppressed [131]. Current findings have suggested benefits mostly in females with decreases in spike frequency [132]. …”
Section: Immunity and Anti-inflammatory Therapies In Epilepsymentioning
confidence: 99%